PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN REPRESENTASI MULTIPEL MATEMATIS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KUANTUM - Sarah Inayah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Mathematical problem solving and multiple representation ability is essential to develop. So it needs a study to facilitate the students to be active, interesting and challenging for students to think and therefore contributes to the students ability to represent, understand the material during learning process and solve mathematical problems. Quantum learning model puts students on comfortable and pleasant condition so that students can play an active role in the learning process and student expected to get the flexibility to bring their own representation and easy to solve the problem. The main objective of this study was to determine the improvement in the mathematical problem solving and multiple representation of students who obtain quantum learning model and students who received conventional learning, as well as to determine the relationship between the mathematical problem solving and multiple representations. This research is a quasi experimental with non equivalent control group design. The population of this study are all students of class VII with two classes of them as samples. The research data obtained through problem-solving ability and multiple mathematical representations test. The results showed that: (a). Quantum learning model can improve the mathematical problem solving and multiple representations ability, (b). there is a relationship between the mathematical problem solving and multiple representations ability.